Evaluation of Trace Lead, Chromium and Cobalt Level in the Urine Samples of Industrial Workers - Ahmed Fadhil Khudhair (Journal of Global Pharma Technology, 2018)
For clinical reasons, and in order to control minimise the effects on the health of individuals exposed to toxic elements, it is most important to monitor concentrations of trace elements in biological materials. Such an examination was achieved for urine samples of workers with different occupations and of different ages. Concentrations of lead, chromium and cobalt were examined in forty urine samples using the flame atomic absorption spectroscopy (F-AAS) technique. The average concentrations of Co, Cr and Pb were 0.0069 to 0.0484 ppm, 0.1056 to 0.9645 ppm and 0.1188 to 0.5067 ppm, respectively. A low detection limit for Co was registered compared to the Pb and Cr. This study has shown that Cr concentrations in the urine samples of people who work in oil refineries were higher than for people working in other vocations. Concentrations of trace Co, Cr and Pb in the urine of people aged 30-40 years were larger than the concentration found for individuals in other age groups. The T-test, F-test and ANOVA have been used to examine the accuracy and precision of results and compare them with those published in the literature (literature review results).Keywords: Lead, Chromium, Cobalt, Urine, FAAS.